Recenzja. Nagoski, E. (2021). Ona ma siłę. Przełomowy poradnik o seksualności kobiet. Warszawa: Grupa Wydawnicza Foksal - Pilarska, Natalia (Przegląd Psychologiczny, 2022)
Recenzja: Nagoski, E. (2021). Ona ma siłę. Przełomowy poradnik o seksualności kobiet. Warszawa: Grupa Wydawnicza Foksal